2019
DOI: 10.18632/oncotarget.27190
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD24 in multiple myeloma tumorigenicity and effects of the microenvironment on its expression

Abstract: Multiple myeloma (MM) is an incurable neoplasm characterized by infiltration of malignant plasma cells (PCs). Recently, the tumor microenvironment has become of great interest in MM as it known to be involved in progression and metastasis of the disease. CD24, is an adhesion molecule expressed during B cell maturation, is down regulated through the cells differentiation into PCs. Though the role of CD24 in solid cancers is well defined, its role in MM remains unknown. We aimed to understand the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…CD24, which was originally identified as a B cell differentiation marker (100), has been indicated as a CSC marker in several tumors, such as ovarian (101), colorectal (102), bladder (103) and urothelial (104) cancers. CD24 has been directly correlated with disease progression and metastasis (59,60,105,106). CD24 is a glycoprotein having both N-and O-linked type glycosylation and linked to glycosylphosphatidylinositol (61).…”
Section: Glycosylation Of Csc Markersmentioning
confidence: 99%
“…CD24, which was originally identified as a B cell differentiation marker (100), has been indicated as a CSC marker in several tumors, such as ovarian (101), colorectal (102), bladder (103) and urothelial (104) cancers. CD24 has been directly correlated with disease progression and metastasis (59,60,105,106). CD24 is a glycoprotein having both N-and O-linked type glycosylation and linked to glycosylphosphatidylinositol (61).…”
Section: Glycosylation Of Csc Markersmentioning
confidence: 99%
“…The important role of CD24 protein expression in MM in vitro was confirmed by our group. CD24+ MM PCs were characterized by a less tumorigenic phenotype than CD24− MM PCs [ 11 ]. Previous publications have shown that CD24 mRNA expression is correlated with good prognosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In MM PC, CD24 mRNA has been shown to be downregulated, correlated to worse OS [ 12 ]. We found that by upregulating CD24 expression in MM cell lines, the cells were less tumorigenic in their phenotype, as assessed by their impaired capability to migrate and to create colonies in culture [ 113 ]. The decreased tumorigenicity correlated with a “more normal” PC immunophenotype in patients with MM and correlated with CD45 expression [ 113 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that by upregulating CD24 expression in MM cell lines, the cells were less tumorigenic in their phenotype, as assessed by their impaired capability to migrate and to create colonies in culture [ 113 ]. The decreased tumorigenicity correlated with a “more normal” PC immunophenotype in patients with MM and correlated with CD45 expression [ 113 ]. Furthermore, following immunophenotype analysis in 124 MM patients treated with bortezomib, cyclophosphamide, and dexamethasone, we found that elevated CD24 expression on PC at diagnosis correlated significantly with longer PFS and OS (Gross Even-Zohar N, et al, submitted).…”
Section: Introductionmentioning
confidence: 99%